KEMAMPUAN PREDIKSI RASIO KEUANGAN DAN UKURAN BANK PADA RISIKO GAGAL BANK - Purnamandari, Ni Putu Ayu Lisna; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 12 No 2 (2015), 2015)
Every Company including banking industry vulnerable to failure. When a bank failure, the impact caused a very large not only harming investor, employee, and customers, but also the state, therefore need an indicator to predict the failure. This study uses financial ratios and bank size as an indicator to predict the risk of bank failure. This research was conducted at the banks listed on the Indonesia Stock Exchange 2009-2013. This study used purposive sampling with a sample size of 22 bank. The result of the study  with the technique Regression analysis concludes that financial ratios are CAR, NPL, ROA and Size Bank is able to predict the risk of bank failure.
Keywords: CAR , NPL , ROA, bank size , the risk of bank failure